On aging : revolt and resignation - Améry, Jean (Indiana University Press, 1994)
On Aging, the first of Jean Amery's books after At the Mind's Limits, is a powerful and profound work on the process of aging and the limited but real defenses available to those experiencing the process. Each essay covers a set of issues about growing old. "Existence and the Passage of Time" focuses on the way aging makes the old progressively see time as the essence of their existence. "Stranger to Oneself" is a meditation on the ways the aging are alienated from themselves. "The Look of Others" treats social aging - the realization that it is no longer possible to live according to one's potential or possibilities. "Not to Understand the World Anymore" deals with the loss of the ability to understand new developments in the arts and in the changing values of society. The fifth essay, "To Live with Dying," argues that everyone compromises with death in old age (the time in life when we feel the death that is in us). Here Amery's intention, as encapsulated by John D. Barlow, becomes most clear: "to disturb easy and cheap compromises and to urge his readers to their own individual acts of defiance and acceptance."